Estudio de las interferencias del Inmunoanálisis en la cuantificación de hormonas tiroideas: Revisión sistemática - Quevedo Reyes, Alisson Gabriela (2025)
Immunoassays are essential tools for quantifying thyroid hormones and are widely used in diagnosing disorders such as hypothyroidism and hyperthyroidism. However, several factors can interfere with their accuracy, leading to altered results and affecting clinical interpretation. The main interferences include biotin, macro-TSH, heterophile antibodies, and autoantibodies against thyroid hormones, all of which can cause erroneous measurements, impacting patient diagnosis and treatment. A systematic literature review was conducted using the PubMed, Lilacs, and ScienceDirect databases, selecting 12 studies published between 2014 and 2024. The included articles were assessed using the JBI tool, revealing a low risk of bias. Biotin interference was reported in 58.3% of the analyzed studies, followed by macro-TSH in 33.3% and heterophile antibodies in 25%. The most frequent effects included an overestimation of T3 and T4 levels, along with a reduction in TSH, potentially leading to a false diagnosis of thyroid disorders. Strategies to mitigate these interferences, such as polyethylene glycol (PEG) precipitation and streptavidin-coated beads, were analyzed and demonstrated significant efficacy. The study concluded that recognizing interferences in immunoassays is essential for improving diagnostic accuracy and preventing errors in thyroid function assessment. Therefore, implementing methodologies to minimize their impact will contribute to more reliable diagnoses and better clinical decision-making